Broadband piezoelectric energy harvesting induced by mixed resonant modes under magnetic plucking - Lo, Y.C.; Chen, C.C.; Shu, Yi-Chung; Lumentut, Mikail (2021)
A piezoelectric device connected to the standard interface circuit is proposed for harvesting energy by inducing the mixed resonant modes of vibration under the two-point rotary magnetic plucking. It consists of a piezoelectric cantilever beam attached to a tip magnet and a second magnet placed on the middle of the beam. Both magnets are excited by another two magnets aligned radically and attached to a rotating host. The two impulsive forces from these magnets are made in opposite directions for the ease of inducing the second resonant mode. As a result, the harvester device exhibits the pronounced broadband energy harvesting which can not be achieved by the conventional design based on the one-point magnetic plucking for exciting a single resonant mode. The analysis is based on the Fourier decomposition of magnetic impulsive forces for realizing the phenomenon of frequency up-conversion. In addition, the estimate of harvested power is analytically derived based on using the equivalent load impedance which is originally proposed for analyzing harvester arrays. The result shows that the theoretical prediction agrees well with the experimental observation. Further, the rotary frequency response exhibits the remarkable feature of broadband energy harvesting as the output power is increased up to 2500% higher than that in the off-resonance region of the setup allowing plucking only on the tip magnet.